Q: How do you solve -7x plus 6 plus 7x-2?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

6 = 7x + x First, add 7x and x.6 = 8xNow, divide both sides by 8.6/8 = xSimplify the answer.3/4 = x.

x2 + 7x + 6 = (x + 6) (x + 1)

x2+7x=-2x2+6 3x2+7x-6=0 (3x-2)(x+3)=0 3x-2=0 or x+3=0 x=2/3 or x=-3

-1.5

9x-4 = 7x+8 9x-7x = 8+4 2x = 12 x = 6

Related questions

x3 - 7x2 + 6x =x (x2 - 7x + 6) =x (x - 6) (x - 1)

Try to factor the left side and set each of the linear expressions equal to zero. 7x^2 +8x -12= 0 (7X-6)(X+2)=0 7X-6=0 X=6/7 X+2=0 X=-2

(7x + 2)(x - 3)

(x - 3)(7x + 2)

(7x + 6)(x - 2)

7x2-19x-6 7*6=427x2-2x+21x-6[7xx 2x] [3*7x 2*3]x(7x-2)+3(7x-2)Answer: (7x-2)(x+3)

7x+6 = -3x-24 7x+3x = -24-6 10x = -30 x = -3

7x-4=x+2 7x=x+2+4 7x=x+6 7x-x=6 6x=6 X=1

4x+9 = 7x+3 4x-7x = 3-9 -3x = -6 x = 2

6 = 7x + x First, add 7x and x.6 = 8xNow, divide both sides by 8.6/8 = xSimplify the answer.3/4 = x.

x3 - 7x2 + 6x = x(x2 - 7x + 6) = x(x2 - x - 6x + 6) = x[x(x - 1) - 6(x - 1)] = x2(x - 1) - 6x(x - 1) = (x2 - 6x)(x - 1)

7x2+49x-42 = 7(x2+7x-6)